Synthetic Biology - Metabolic Engineering - Zhao, Huimin; Zeng, An-Ping.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book review series presents current trends in modern biotechnology. The aim is to cover all aspects of this interdisciplinary technology where knowledge, methods and expertise are required from chemistry, biochemistry, microbiology, genetics, chemical engineering and computer science. Volumes are organized topically and provide a comprehensive discussion of developments in the respective field over the past 3-5 years. The series also discusses new discoveries and applications. Special volumes are dedicated to selected topics which focus on new biotechnological products and new processes for their synthesis and purification. In general, special volumes are edited by well-known guest editors. The series editor and publisher will however always be pleased to receive suggestions and supplementary information. Manuscripts are accepted in English.
Promoters and terminator discovery and engineering -- Engineering and Evolution of Saccharomyces cerevisiae to Produce Biofuels and Chemicals -- Corynebacterium glutamicum for Sustainable Bioproduction: From Metabolic Physiology to Systems Metabolic Engineering -- Orthogonal Protein Translation Using Pyrrolysyl-tRNA Synthetases for Single and Multiple-Noncanonical Amino Acid Mutagenesis -- Synthetic Biology for Cell-Free Biosynthesis: Fundamentals of Designing Novel In Vitro Multi-Enzyme Reaction Networks -- Molecular engineering of synthetic metabolic pathways -- Pathway Design, Engineering and Optimization -- Xenobiology: State-of-the-art, Ethics and Philosophy of new-to-nature organisms.
Keywords: Biotechnology; Bioinformatics; Industrial microbiology; Proteins .; Chemical Bioengineering; Computational and Systems Biology; Industrial Microbiology; Protein Biochemistry